2021
DOI: 10.1103/physrevb.104.075148
|View full text |Cite|
|
Sign up to set email alerts
|

Electronic nature of chiral charge order in the kagome superconductor CsV3Sb5

Abstract: Kagome superconductors with T C up to 7 K have been discovered for over 40 y. Recently, unconventional chiral charge order has been reported in kagome superconductor KV 3 Sb 5 , with an ordering temperature of one order of magnitude higher than the T C . However, the chirality of the charge order has not been reported in the cousin kagome superconductor CsV 3 Sb 5 , and the electronic nature of the chirality remains elusive. In this paper, we report the observation of electronic chiral charge order in CsV 3 Sb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(76 citation statements)
references
References 62 publications
(111 reference statements)
7
64
0
Order By: Relevance
“…Due to their inherent geometric frustration and unique band structure, kagome materials [1] represent an excellent platform for discovering, classifying and under-standing correlated electronic phases of quantum matter [2][3][4][5][6]. The novel family of kagome metals AV 3 Sb 5 (A = K, Rb, Cs) [7][8][9][10][11] exhibit an array of interesting effects such as giant anomalous Hall conductivity [12,13], charge order [11,[14][15][16][17][18][19][20][21][22], orbital order [23], and possible unconventional superconductivity [7,8,10]. An important feature of the charge order, which onsets at temperatures T co ∼ 100 K at ambient pressure, is the breaking of time-reversal symmetry, as reported by scanning tunneling microscopy (STM) measurements [11,14,15,17] in (K,Rb,Cs)V 3 Sb 5 , by muon spin relaxation (µSR) in KV 3 Sb 5 [24] and CsV 3 Sb 5 [25], and by Kerr effect measurements in CsV 3 Sb 5 [26].…”
mentioning
confidence: 99%
“…Due to their inherent geometric frustration and unique band structure, kagome materials [1] represent an excellent platform for discovering, classifying and under-standing correlated electronic phases of quantum matter [2][3][4][5][6]. The novel family of kagome metals AV 3 Sb 5 (A = K, Rb, Cs) [7][8][9][10][11] exhibit an array of interesting effects such as giant anomalous Hall conductivity [12,13], charge order [11,[14][15][16][17][18][19][20][21][22], orbital order [23], and possible unconventional superconductivity [7,8,10]. An important feature of the charge order, which onsets at temperatures T co ∼ 100 K at ambient pressure, is the breaking of time-reversal symmetry, as reported by scanning tunneling microscopy (STM) measurements [11,14,15,17] in (K,Rb,Cs)V 3 Sb 5 , by muon spin relaxation (µSR) in KV 3 Sb 5 [24] and CsV 3 Sb 5 [25], and by Kerr effect measurements in CsV 3 Sb 5 [26].…”
mentioning
confidence: 99%
“…The exotic CDW states without electron-phonon coupling (EPC) mechanism [9] display many unconventional characteristics. The CDWs in these three compounds exhibit chiral anisotropy [11][12][13] and reduce the density of electronic states near the Fermi level [11,[14][15][16]. Various evidence including giant anomalous Hall response even without magnetic field [17,18], the chirality of CDW that can be tuned by a magnetic field [11][12][13], edge supercurrent [19] and spontaneous internal magnetic field [20] indicates that the charge order may break the time-reversal symmetry, which has also been verified theoretically [11,21,22].…”
mentioning
confidence: 81%
“…The CDWs in these three compounds exhibit chiral anisotropy [11][12][13] and reduce the density of electronic states near the Fermi level [11,[14][15][16]. Various evidence including giant anomalous Hall response even without magnetic field [17,18], the chirality of CDW that can be tuned by a magnetic field [11][12][13], edge supercurrent [19] and spontaneous internal magnetic field [20] indicates that the charge order may break the time-reversal symmetry, which has also been verified theoretically [11,21,22]. Moreover, it has been found that CsV 3 Sb 5 samples have the roton pair density wave [7], which is analogous to the one in unconventional high-T c cuprate superconductors [23].…”
mentioning
confidence: 99%
“…One of the key features of the AV 3 Sb 5 family is the formation of a density-wave state accompanied by a superstructure [9]. While there is a consensus on the 2 × 2 in-plane modulation [22,[41][42][43][44][45], both two-fold and fourfold modulations along the c axis have been proposed [23,44,46,47]. This superstructure formation is concomitant with the reduction in the density of states at the Fermi level.…”
Section: Energy Scale Of the Charge-density Wavementioning
confidence: 99%